UPAYA MENIGKATKAN KOMPETENSI PEDAGOGIK GURU DALAM PERENCANAAN DAN PELAKSANAAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SMP NEGERI SATAP 2 GOLEWA TAHUN PELAJARAN 2023/2024 - Dhiu, Imelda (Jurnal Analisis Pendidikan Sosial, 2024)
This research aims to enhance the pedagogical competence of teachers at SMP Negeri Satap 2 Golewa through academic supervision by the school principal. Learning in the school remains a challenge, particularly concerning the pedagogical competence of teachers. The research method employed is action research, conducted in three stages: preparation, implementation, and evaluation, along with reflection, carried out in at least two cycles. Data were gathered through classroom observations, feedback, and documentation. The results indicate that academic supervision effectively improves the pedagogical competence of teachers.